Austerity, political control and supplier selection in English local government: implications for autonomy in multi-level systems - Peter Eckersley; Anthony Flynn; Laurence Ferry; Katarzyna Lakoma (Public Management Review, 2021)
Analysis of 60,000 contracts awarded by English councils between 2015–19 reveals that austerity constraints are a key predictor of councils outsourcing services to for-profit suppliers, regardless of their political control. Conservative Party-controlled councils are also more likely to contract with for-profit suppliers, although we found no link between Labour-controlled councils and not-for-profit suppliers, nor evidence that political or budgetary factors influence whether councils contract with providers based in their own region. We argue that centrally imposed funding cuts, and a belief that for-profit suppliers represent a cheaper option, could be overriding Labour Party councils' ideological preference for not-for-profit providers.
Keywords: 710; Public contracting; political control; austerity; local government; procurement